Letter from Carl D. Duncan to Patricia Whiting, December 10, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan discusses photographs and wishes Whiting well on her upcoming trip to San Francisco.